PENGARUH UPAH MINIMUM, TINGKAT PENDIDIKAN DAN USIA TERHADAP PENYERAPAN TENAGA KERJA DI JAWA TIMUR TAHUN 2017-2021 - Larassanti Defina Rizka Faza; Moh. Khusaini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The objective of this research is to discuss and analyze the effect of minimum wage, education level and age on labor force absorption in 38 regencies and cities in East Java. A 2017-2021 data was examined using Fixed Effect Model. The results of the analysis indicate that Municipal Minimum Wage negatively and significantly influences the labor absorption in regencies and cities in East Java, that age positively and significantly influence the labor absorption in regencies and cities in East Java, and that education level negatively but insignificantly impacts the labor absorption in regencies and cities in East Java.